Comparação entre métodos diagnósticos da tuberculose em bovinos abatidos em matadouros-frigoríficos do Estado de São Paulo - Silva, David Attuy Vey da [UNESP] (2015)
Tuberculosis is a contagious infectious zoonotic disease of high importance in public health, which diagnosis and the epidemiology knowledge are essentials in this disease prevention and control. This study aimed to compare the different diagnostic tests for bovine tuberculosis. Microbiological culture, histopathological and molecular M. bovis diagnosis were made in adults bovines slaughtered in slaughterhouses under Inspection Federal Service - SIF in São Paulo State and after, the animals origin municipalities were geoprocessing. Samples of lymph nodes with macroscopic lesions suggestive of tuberculosis were identified and collected during the animals' slaughter. The microbiological diagnosis was made by culture in solid medium, histopathological characterization by staining with hematoxylin eosin (HE), identification of AFB by Ziehl-Neelsen (ZN) and the diagnosis by molecular identification was carried out from DNA extracted from the lesions suggestive of tuberculosis by polymerase chain reaction (PCR, nested PCR and multiplex PCR) and the DNA extracted from the colonies was isolated for M. bovis identification using PCR and multiplex PCR. Most injuries (50% - 25/50) was identified in retropharingeal and all of them were characterized as caseous. M. bovis colonies growth was characteristics in 56% (28/50) of the samples and64% (32/50) of the samples were positive by HE staining and 52% (26/50) for confirmatory ZN staining. The PCR directly from tissue showed 38% (19/50) of positive samples and the PCR from the colonies showed 56% (28/50) of positive samples. The kappa test (95%) between the diagnoses showed higher agreement between the molecular diagnostics of the colonies, followed by histopathological and molecular analysis of tuberculosis suggestive lesions toward the microbiological diagnosis. The highest sensitivity and specificity values were observed in the colonies molecular testing, followed by histopathological and ...